Analysis of Landslide Potential Based on Magnetic Susceptibility of Rocks Using Geomagnetic Methods in Suka Damai Village, Bulango Utara Subdistrict, Bone Bolango Regency - Yunginger, Raghel; Sandi, Febriyanti Yuliana; Setiawan, Dewa Gede Eka; Husen, Maman Hermana; Zulkifli, M; Ardiyanto, Kamal (Universitas Negeri Surabaya, 2024)
Landslides in Bone Bolango Regency have increasingly impacted the population, with data showing a rise in affected areas from 2020 to 2021. To mitigate these risks, mapping areas with potential landslides is crucial for providing early warnings, although such efforts remain incomplete. Therefore, this research aims to determine the potential for landslides in Bone Bolango Regency, especially in Suka Damai Village. The geophysical method used in this research is the geomagnetic method because it utilizes the magnetic properties of rocks below the surface and can interpret subsurface structures in areas with the potential for landslides. Based on the research results, it was identified that the research location is dominated by diorite and granodiorite igneous rocks, where diorite rocks dominate from the surface to a depth of 40 meters with a susceptibility contrast value of 3 – (2.5) SI. Meanwhile, granodiorite rocks are found at a 20 – 110 m depth with a susceptibility value of 1.5 – 3 SI. Based on 3D visualization, it was found that diorite rock acted as landslide material, and granodiorite rock acted as sliding rock. Besides that, material movement forms slopes caused by shear failure that occurs along one or more landslide planes. This research confirms that the research area is a potential landslide area with a level of stability in category D, which means it is less stable.